Efficacy and safety analysis of combination therapy based on mitoxantrone hydrochloride liposome injection (Lipo-MIT) in relapsed/refractory NK/T-cell lymphoma - Wang, Xing-long; Wang, He-nan; Yang, Lei; Yang, Jing; Cong, Jia; Song, Zhi-hui; Wang, Liang (Frontiers in Oncology, 2024)
Background Currently, there is no standard treatment for relapsed/refractory NK/T-cell lymphoma (NKTCL). Liposomal mitoxantrone (Lipo-MIT) showed good anti-tumor effect in patients with NKTCL, breaking the limitation of natural resistance of NKTCL to anthracyclines. To further improve the efficacy, we tried a combination therapy based on Lipo-MIT in patients with relapsed/refractory NKTCL. Methods 12 patients with relapsed/refractory NKTCL were enrolled in this retrospective study, all of whom had previously received pegaspargase-based treatments. The salvage treatment was a combination regimen based on Lipo-MIT. The efficacy was evaluated after every two cycles. Results 11 patients had stage IV NKTCL, and all but one patients had an NRI score of ≥3. The median previous lines of treatment was two (range, 1–4), and five patients were refractory to their last line of treatment. The best response rates were as follows: complete response (CR) in five (41.7%) patients, partial response in five (41.7%) patients, stable disease in one (8.3%) patient, and progressive disease in one (8.3%) patient. At a median follow-up of four months (range, 2–14), seven patients died, with a median PFS of five months and a median OS of seven months. The six-month PFS and OS rate was 44.4% and 52.1%, respectively. All patients had suffered from side effects, among which myelosuppression was most reported. Nine patients had grade three or more myelosuppression, and the median recovery time from myelosuppression was 14 days (2–35 days). Five patients had obvious skin hyperpigmentation, and the CR rate was significantly higher compared with those without skin hyperpigmentation (80% vs. 14.3%, p=0.023). Other side effects included liver insufficiency (N=4), coagulation dysfunction (N=4), acute pancreatitis (N=2), and immunotherapy-related adverse effects (irAEs, N=2). Conclusion Combination therapy based on Lipo-MIT has a high remission rate for relapsed/refractory NKTCL, but the duration of remission needs to be further extended. Lipo-MIT has obvious myelosuppression toxicity, and active supportive therapy should be given when combined with other cytotoxic drugs.